Preterm Labour Pain & Its Outcome in 50 pts attending at a Tertiary Care Hospital-ICMH - Jabeen, Mahe; Jebunnesa; Dilruba Akter, Mossammat; Ara, Anjuman; Azmaeen, Md Shabab (Medicine Today, 2023)
Introduction: Preterm labor is the leading cause of neonatal morbidity all over the world. Over the past two decades despite major preventive efforts, the incidence of preterm birth has remained constant at about 5-10% of live births. The etiology is often multifactorial and poorly understood. Currently preterm labour is one of the most challenging problems confronting the obstetricians and perinatologists. With this background the present study was done to find out perinatal outcome in women presenting with preterm labour. Aims To study the fetal and maternal outcome in preterm labor cases. Materials and Methods: It was Prospective, single centered, observational study. A total of 50 women with preterm labor in the study period i.e. from June 2019 to May 2020 were included for the study sample. This study carried out at the department of Obstetrics and Gynecology, Institute of Child and Mother Health (ICMH), Matuail, Dhaka, Bangladesh. The data were collected personally through a structural questionnaire. Results: Out of 50 subjects, majority of mothers 32(64%) were in age group of 21-30 years followed by 12(24%) in age group of 20 years. Majority 26(52%) of study subjects were primigravida followed by 24(48%) multigravida. Majority 32(64%) of study subjects were in lower class followed by 15 (30%) cases in middle class, 3(6.0%) cases in affluent class. Maximum 31 (62%) cases were unbooked cases and rest 19 (38%) cases were booked. Out of 50 babies who were <2500 grams, maximum 29 (58.0%) were low birth weight followed by 11(22%) being VLBW babies. 5 cases were >2.5 kgs, which are not LBW babies according to WHO Classification of low birth weight. Majority 17 (47.2%) stayed for 1-10 days followed by 9 (25.0%) babies for 11-20 days. Also 7 (19.4%) babies stayed for 21-30 days. Conclusions: Preterm infants are at high risk of overall morbidity and mortality. Clinical suspicion, early detection and correction of risk factors, institutional delivery and good neonatal care back up facilities can improve the outcome of preterm labour and decrease the maternal complications as well. Medicine Today 2023 Vol.35 (2): 73-77